The Existence of High Heirloom Assets in Nagari Muaro Paiti and Their Relevance to Contemporary Islamic In Heritance - Rahmad, Beni; Yenti, Endri; Alwana, Hanif Aidhil (Alhurriyah, 2022)
High heirloom assets are assets that are jointly owned by a people who have blood ties and are inherited from generation to generation from previous ancestors, and these assets are under the management of the head of the inheritance (eldest male in the clan). High heirlooms do not belong to individuals, but belong to a group together. Inheritance from high inheritance applies a collective system, namely the property is not divided and delivered to the recipient group in the form of an undivided unit. To guarantee land ownership for its people, the government makes rules regarding land ownership, namely Law no. 5 of 1960. With this law, many people have certified their land, including high inheritance in the form of ulayat land in Muaro Paiti village, as private property rights recognized by law. As a result of the certificate of high inheritance into private property, of course, the system of inheritance of high inheritance has changed into inheritance according to the laws in force in Indonesia, namely Islamic inheritance.